A Kinetic Approach to the Oxidation of Some Perfumery Alcohols by N-Bromosuccinimide in Alkaline Medium - Prabhu, D.V.; Parbat, H.A. (Asian Journal of Chemistry, 2011)
The aliphatic alcohols, 2-propanol, 2-butanol and 3-methyl-1-butanol are extensively used as diluents in the manufacture of perfumes. Secondary alcohols, borneol, isoborneol and menthol are used in the preparation of fragrances, flavours and cosmetics. The pseudo first order kinetics of the oxidation of these alcohols has been studied using N-bromosuccinimide in alkaline medium as the oxidant. The progress of the reaction was monitored by iodometric titration of the unreacted oxidant at regular time intervals. The rate constants (k) of the oxidation reaction were determined from the straight lines plots of log (a-x) versus time. The effects of (i) alcohol concentration (ii) oxidant concentration (iii) ionic strength (iv) temperature in the range 303-318 K on the oxidation rate has been studied in detail. It was observed that the reaction rate increases with [Alc] but decreases with oxidant concentration. The oxidation rate increases with ionic strength. From the effect of temperature on the reaction rate, the energy of activation and other thermodynamic activation parameters, ΔH*, ΔG* and ΔS* have been evaluated. Suitable reaction mechanism and rate laws have suggested for the oxidation process. The oxidation rates follow the sequence: (1) for aliphatic alcohols, 2-propanol > 2-butanol > 3-methyl-1-butanol, which has been explained on the basis of chain length. (2) for secondary alcohols borneol > isoborneol > menthol, which has been explained on the basis of structures, steric factors and isomeric characteristics of the alcohols under study.